Outcome of Hyperthyroidism Therapy by Radioactive Iodine (I-131) Using a Fixed Dose in Combination with a Radioactive Iodine Uptake - Roysri, Krisana (Srinagarind Medical Journal, 2024)
Background and Objective: The treatment of thyroid toxicity using iodine-131 (I-131) radioiodine therapy is an efficient and economically viable approach for patient care. The adjustment of radiation dosage for patients depends on the specific abnormalities of their thyroid glands. The study aimed to investigate outcomes of treating thyroid toxicity with I-131 at Surin Hospital, emphasizing the significance of optimizing radiation dosage for effective and economical patient care. Methods: This study was descriptive retrospectively analyzed 195 hyperthyroid patients treated with radioactive iodine treatment (RAIT); 183 of whom underwent radioactive iodine uptake test (RAIU). Results: At a first year, the remission rate was 78.14% (p < 0.001). The mean ± SD dose of I-131 was 20.36 ± 5.74 mCi. Age, sex, and RAIU were not associated with the remission (p > 0.05). However, males tended to have a lower remission rate than females (p = 0.07). In one patient, the results of the RAIU changed the diagnosis to thyroiditis, thus avoiding unnecessary RAIT. Conclusions: The treatment for hyperthyroidism at Surin Hospital has a high success rate during the first year. This is because the amount of radiation used is quite high and measuring the amount of radiation on the neck helps in diagnosing patients with thyroiditis. This prevents patients from being exposed to unnecessary radiation.